2020
DOI: 10.1055/s-0040-1713628
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Traumatic Encephalopathy and Neuropathological Comorbidities

Abstract: AbstractWith age, the presence of multiple neuropathologies in a single individual becomes increasingly common. Given that traumatic brain injury and the repetitive head impacts (RHIs) that occur in contact sports have been associated with the development of many neurodegenerative diseases, including chronic traumatic encephalopathy (CTE), Alzheimer's disease, Lewy body disease, and amyotrophic lateral sclerosis, it is becoming critical to understand the relationship and intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 126 publications
0
7
0
Order By: Relevance
“…For example, cardiovascular risk factors are strongly correlated with sporadic AD ( Leszek et al, 2020 ). Another significant risk factor for sporadic AD is TBI, especially chronic traumatic encephalopathy ( Van Den Heuvel et al, 2007 ; Stein and Crary, 2020 ). AD is characterized by decreased blood flow in the brain and dysfunction of the neurovascular unit, which likely causes impaired oxygenation ( Ahmad et al, 2020 ; Yu et al, 2020 ).…”
Section: Role Of Hif-1α In Neurodegenerative Diseasesmentioning
confidence: 99%
“…For example, cardiovascular risk factors are strongly correlated with sporadic AD ( Leszek et al, 2020 ). Another significant risk factor for sporadic AD is TBI, especially chronic traumatic encephalopathy ( Van Den Heuvel et al, 2007 ; Stein and Crary, 2020 ). AD is characterized by decreased blood flow in the brain and dysfunction of the neurovascular unit, which likely causes impaired oxygenation ( Ahmad et al, 2020 ; Yu et al, 2020 ).…”
Section: Role Of Hif-1α In Neurodegenerative Diseasesmentioning
confidence: 99%
“…However, the occurrence of multiple pathologies also increases with age, and the studies reviewed here indicate that is also true for CTE cases with an older age at death. The development of comorbid pathology is likely related to age, the severity and amount of exposure to repetitive head injury, and other individual genetic and environmental factors [ 83 ]. With increased global brain banking efforts, there will be an increased frequency of CTE cases with an older age at death and comorbid pathology.…”
Section: Discussionmentioning
confidence: 99%
“…For a detailed description and visualisation of CTE pathological features see reference [ 57 ]. These diagnostic criteria allow for more standardised classification of CTE pathology, but it is widely acknowledged that multiple neuropathologies such as CTE p-tau lesions, beta-amyloid plaques, cerebral amyloid angiopathy, Lewy body disease, and TDP-43 proteinopathy can be present in the brain of a single individual, and that this cooccurrence is more common with increasing age [ 83 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, dynactin pathology and p50-positive NCIs remained unseen in ALS, FTLD-MND, and HpScl [7]. Recently, multiple neuropathologies have received much attention [27,28]. A study of aged persons revealed that about 80% of participants had comorbid multiple neuropathologies, including TDP-43 pathology, at autopsy [29].…”
Section: Pathology Of Perry Diseasementioning
confidence: 99%